Strategi Pemasaran Masa Depan: Mengurai Peran Sales Promotion yang Inovatif dan Daya Tarik Celebrity Endorser dalam Membimbing Keputusan Pembelian Konsumen - Tianingrum, Destri Mailinda; Rahayu, Agus; Dirgantari, Puspo Dewi (Ekonomis: Journal of Economics and Business, 2024)
Fashion has a strong appeal and is accepted by individuals of all ages as a determining aspect of clothing and daily lifestyle. The purpose of this study was to examine the impact of sales promotion on consumer purchasing choices. The target population of this study consists of Billionaire's Project consumers, with a sample of 100 respondents selected through purposive sampling, a non-probability sampling technique. To collect data, questionnaires were distributed to individuals who had purchased and used products from the Billionaire's Project. The data analysis process uses descriptive and inferential analysis using the Partial Least Square (PLS) 4.0 analysis tool. The findings of this study confirm that sales promotion has a significant effect on purchasing decisions, and the involvement of celebrity endorsers also has a significant influence on consumer purchasing choices. Business owners can leverage these research findings as valuable references when designing digital marketing strategies geared toward increasing sales of Billionaire's Project products, particularly in the areas of sales promotion and celebrity-based marketing.